Criticism of Murabahah Practices in Islamic Banks: Between Fiqh Ideals and Banking Reality - Rinaldy, Fachri; Dongoran, Irham; Rivai, Andri; Muhammad Akbar, Jalaluddin; Rabbani, Muhammad Naufal (JPS (Jurnal Perbankan Syariah), 2026)
The development of Islamic banking in Indonesia shows that the use of murabahah contracts is more dominant than profit-sharing contracts such as mudharabah and musyarakah. This occurs because murabahah is considered simpler to implement and involves lower risks. Purpose: This study aims to examine the extent to which murabahah financing practices in Islamic banks comply with the principles of muamalah fiqh. Method: This research uses a normative legal method with a normative–critical approach by analyzing various sources, including literature on fiqh and Islamic economics, articles from scientific journals, fatwas issued by the Dewan Syariah Nasional–Majelis Ulama Indonesia, and official reports from the Otoritas Jasa Keuangan as the basis for theoretical and empirical analysis. Findings: The findings indicate that the practice of murabahah in Islamic banks has not fully complied with sharia principles, particularly regarding the obligation of ownership of goods, the clarity of the cost price, and the application of murabahah contracts in inappropriate contexts, which in some cases makes it resemble interest-based financing mechanisms. Implication: This study implies the need to strengthen compliance with sharia principles and to apply the values of muamalah fiqh more comprehensively in Islamic banking financing practices